2011
DOI: 10.1097/iae.0b013e3181f049bd
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Vitelliform Detachment in Patients With Subretinal Drusenoid Deposits (Reticular Pseudodrusen)

Abstract: PURPOSE: To report a recently observed association of macular vitelliform detachment and subretinal drusenoid deposits (reticular pseudodrusen). METHODS: Clinical and multimodal imaging data of patients with acquired vitelliform lesions in association with subretinal drusenoid deposits were reviewed. Acquired vitelliform lesions were defined as subretinal accumulations of yellow material that developed in adulthood. Subretinal drusenoid deposits were diagnosed as being present if there were drusen-like accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 11 publications
1
32
0
Order By: Relevance
“…Similarly, in the BMES, after adjusting for age, Joachim et al 8 demonstrated the 15-year cumulative incidence of RPD was twice as likely in females. In the cohort of six patients reported by Zweifel et al, 29 four individuals with AFVD and RPD were female but their series was not consecutive. Gliem et al 8 reported no difference in sex distribution in their study on the association between RPD and PXE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, in the BMES, after adjusting for age, Joachim et al 8 demonstrated the 15-year cumulative incidence of RPD was twice as likely in females. In the cohort of six patients reported by Zweifel et al, 29 four individuals with AFVD and RPD were female but their series was not consecutive. Gliem et al 8 reported no difference in sex distribution in their study on the association between RPD and PXE.…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, very limited literature available on the association of RPD and AFVD. To the best of our knowledge, Zweifel et al 29 were the only group that has reported the association other than in case reports. This was, however, a small study with seven eyes of six patients only, and did not report the prevalence of RPD within eyes presenting consecutively with AFVD.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Although SD-OCT provides more detail about the structure than time-domain OCT, SD-OCT has a limited ability to discriminate diseases that cause similar discrete yellowish-white dots, such as benign retinal flecks [36], Malattia Leventinese (Doyne honeycomb) retinal dystrophy (Zweifel et al IOVS 2011;52:ARVO E-Abstract 3703), and subretinal drusenoid deposits [44].…”
Section: Sd-octmentioning
confidence: 99%
“…These lesions are associated with a variety of retinal disorders, including AMD, central serous chorioretinopathy, Best disease, adult-onset foveomacular dystrophy, vitreomacular traction and epiretinal membrane formation, 94 and pseudoxanthoma elasticum. 6,[95][96][97][98] AVLs appear as a yellow round lesion on clinical examination and CFP and exhibit hyperautofluorescence with FAF. With OCT imaging these lesions display dome-shaped subretinal homogenous hyperreflectivity.…”
Section: Acquired Vitelliform Lesionsmentioning
confidence: 99%